Multi-scale quantile connectedness networks under fintech integration: evidence from China’s financial markets - Shaofeng Zhang; Zheng Zou; Qinghua Zou (Humanities & Social Sciences Communications)
Abstract The integration of fintech into financial markets has significantly reshaped inter-market risk dynamics, raising questions about its impact on systemic risk. However, current research tends to analyze either mean- or quantile-based connectedness only after fintech adoption, leaving unresolved how different shock intensities affect the evolution of systemic risk around the structural break associated with fintech integration. This study investigates the interconnectedness among financial markets before and after the integration of fintech by analyzing risk spillovers under varying degrees of systemic shock, utilizing a multi-scale framework that combines quantile vector autoregression with frequency-domain analysis. We uncover a U-shaped pattern of risk spillovers that varies with the intensity of systemic shocks. Furthermore, the fintech market enhances the bond market’s connectedness with financial markets, demonstrating its robust risk resilience under normal conditions but reducing the resilience during extreme cases. Frequency-domain analysis reveals an inverse trend of time scales in the bond market and a decline in long-term risk spillovers upon fintech incorporation. In the time domain, risk spillovers associated with fintech exhibit greater volatility under normal conditions but tend to stabilize during systemic extremes. Meanwhile, fintech increases the likelihood of left-tail risks in financial markets, indicating heightened downside exposure. These dynamics are further supported by a portfolio-level analysis, which confirms fintech’s role in diversifying risks and the bond market’s function as a safe haven. These findings offer meaningful insights for regulatory risk supervision and investment strategy.